Implementasi Kebijakan Peraturan Presiden Nomor 33 Tahun 2020 Dalam Pelaksanaan APBD Di Kota PasuruanImplementasi Kebijakan Peraturan Presiden Nomor 33 Tahun 2020 Dalam Pelaksanaan Apbd Di Kota Pasuruan - Nizarsyah, Faishal; Priyanto (Soetomo Magister Ilmu Administrasi, 2023)
The regional unit price standard serves as the highest limit in the planning and implementation of the regional revenue and expenditure budget (APBD) in accordance with the mandate of Government Regulation Number 12 of 2019 concerning Regional Financial Management. Presidential Regulation Number 33 of 2020 concerning regional unit price standards (SRUP) is intended as a guideline for regional governments in preparing unit price standards in each region which are then used for the preparation of Work Plans and Budgets for Regional Work Units (RKA-SKPD), Grindle Theory policy implementation includes six things, namely: the interests of the target group, the benefits received, the changes desired, the accuracy of the program, the clarity of the implementor and adequate human resources. The method used in this research is descriptive method. Data collection techniques were carried out using literature studies, field studies, namely participatory observation and interviews. The source of information that the researchers used in this study came from direct interviews with informants, namely employees of the Pasuruan City Government who were directly involved with the planning and implementation of the APBD in Pasuruan City in the Implementation of Presidential Regulation Number 33 of 2020 Policy concerning Regional Unit Price Standards (SHSR) Based on the research that has been carried out, it can be seen that the implementation in the field that occurred in Pasuruan City is related to Presidential Regulation number 33 of 2020, as in Article 3 paragraph 1 of the Presidential Regulation referred to in the aforementioned Presidential Regulation, it is stated that regional heads set standard unit prices for honorarium fees, domestic official travel, meetings or meetings inside and outside the office, procurement of official vehicles, and maintenance according to regional unit price standards. However, the reality on the ground is that many expenditure items have not been regulated in the Presidential Regulation. Keywords: Policy Implementation, standard regional unit price (SRUP)